Case Report: Minimally invasive repair of a traumatic abdominal wall hernia in a child with a fascial closure device - Lu, Huiyu; Zhang, Zemin; Chao, Jun; Zhang, Chuanguang; Zhang, Guoqing; Tao, Shujie; Yan, Qingtao (Frontiers in Surgery, 2024)
Abdominal trauma is common in daily life, but a traumatic abdominal wall hernia (TAWH) in children is rare. A TAWH is caused by a huge external force that leads to subcutaneous muscle and fascia rupture, while the skin remains intact. As abdominal pressure increases, the abdominal contents protrude, forming a lump. A TAWH is highly susceptible to missed diagnosis because of other severe injuries. We report a case of a 2-year-old boy with a TAWH who developed a prominent subcutaneous mass on the right side of his abdomen after abdominal trauma; the size of the mass changed significantly with abdominal pressure and crying. In this case, we used a new approach of laparoscopic suture repair technique with the assistance of a fascial closure device and achieved good results. We found that this method offers the advantages of minimally invasive surgery, fast recovery, and no visible surgical incisions. There was no recurrence after 8 months of follow-up.